Novel and Alternative Therapeutic Strategies for Controlling Avian Viral Infectious Diseases: Focus on Infectious Bronchitis and Avian Influenza - Abbas, Ghulam; Yu, Jia; Li, Guangxing (Frontiers in Veterinary Science, 2022)
1 Growing poultry farming has enabled higher spread of infectious diseases and their pathogens among different kinds of birds, such as avian infectious bronchitis virus (IBV) and avian influenza virus (AIV). The IBV and AIV are potential source to cause mortalities of poultry and economic losses. Furthermore, some pathogens have ability to cause zoonotic diseases and impart human health problem. The antiviral treatments that are being used often lead to the resistance to virus along with the problems of side effects, recurrence and latency of viruses. Though, the target hosts are being vaccinated, the constant emerging and re-emerging of strains these viruses causes disease outbreaks. The pharmaceutical industry is gradually targeting extracts of plants to develop novel herbal drugs with the purpose of proper anti-viral capabilities. The natural therapeutic agents developed from herbs, essential oils, and distillery processes deliver a rich source of amalgams to discover and produce new antiviral drugs. The mechanisms involve have elaborated how these natural therapeutics agents play major role during the entry and replication of virus to host and cause inhibit to viral pathogenesis. Nanotechnology is one of the advanced techniques that can be very helpful to diagnoses and control the infectious diseases of poultry. In general, this review comprises the issue of poultry industry situation, current infectious disease (mainly IB and AI) control measures and furthermore setup of novel therapeutics by using plant extracts and use of nanotechnology information that may help to control these diseases.